The Role of Gravity in the Evolution of the Concentration Field in the Electrochemical Membrane Cell - Batko, Kornelia M.; Ślęzak, Andrzej; Bajdur, Wioletta M. (Entropy (Basel, Switzerland), 2020)
The subject of the study was the osmotic volume transport of aqueous CuSO4 and/or ethanol solutions through a selective cellulose acetate membrane (Nephrophan). The effect of concentration of solution components, concentration polarization of solutions and configuration of the membrane system on the value of the volume osmotic flux ( J v i r ) in a single-membrane system in which the polymer membrane located in the horizontal plane was examined. The investigations were carried out under mechanical stirring conditions of the solutions and after it was turned off. Based on the obtained measurement results J v i r , the effects of concentration polarization, convection polarization, asymmetry and amplification of the volume osmotic flux and the thickness of the concentration boundary layers were calculated. Osmotic entropy production was also calculated for solution homogeneity and concentration polarization conditions. Using the thickness of the concentration boundary layers, critical values of the Rayleigh concentration number ( R C r ), i.e., the switch, were estimated between two states: convective (with higher J v i r ) and non-convective (with lower J v i r ). The operation of this switch indicates the regulatory role of earthly gravity in relation to membrane transport.